Emergence and phenotypic characterization of the global SARS-CoV-2 C.1.2 lineage - Cathrine Scheepers; Josie Everatt; Daniel G. Amoako; Houriiyah Tegally; Constantinos Kurt Wibmer; Anele Mnguni; Arshad Ismail; Boitshoko Mahlangu; Bronwen E. Lambson; Darren P. Martin; Eduan Wilkinson; James Emmanuel San; et al. (Nature Communications, 2022)
The SARS-CoV-2 PANGO lineage C.1.2 has been under monitoring by global health authorities as it has spread worldwide. Here, Bhiman and colleagues characterise the emergence of the lineage, and its neutralisation sensitivity using data from vaccinees and previously infected individuals.